Towards a sustainable green space system: understanding planning and management dynamics in the City of Johannesburg. - Nhlozi, Mduduzi W (My University, 2013)
The notion of green infrastructure brings a new dynamic for dealing with urban problems in a way that responsively addresses urban problems while at the same maintaining the ecological integrity of the natural environment. Key to the notion of green infrastructure is the need to integrate and link green areas with built infrastructure in planning and development processes. Green infrastructure suggests that to achieve sustainable development in urban landscapes, green spaces should be planned for and managed as infrastructure and must be conceived of and understood as a genuinely possible means to improve and contribute to sustainability. Green infrastructure requires an institutional and policy framework that supports practices geared towards planning and managing green assets in the same way in which traditional infrastructure systems are managed. This study explores the planning and management dynamics of green infrastructure in the City of Johannesburg. The study analyses the institutional and policy frameworks of City of Johannesburg to understand these dynamics. One the one hand, the aim is to explore whether green space planning and management is understood in an ‘infrastructural’ sense and on the other, to explore the institutional blockages for green infrastructure planning in the City. The study argues that a number of institutional and implementation challenges for planning and management of green infrastructure exist in Johannesburg. These are the result of an institutional setup which essentially provides fertile ground for some structures to compete against one another rather than work collaboratively in areas that are of common interest. While these challenges exist in the city, it has been established in the study that the City has begun to shift towards green infrastructure practices to address certain urban problems such as flooding and storm-water. For instance, the City is currently deepening its understanding of the concept of Sustainable Urban Drainage Systems (SUDS) to explore how this can contribute towards addressing issue of storm-water management. Important to note that is that while there is this gradual shift towards SUDS, the notion of green infrastructure largely remains at the conceptual level, in relation to particular issues, and is yet to be fully implemented and mainstreamed in the City’s planning processes.
Keywords: Architecture--Environmental aspects; City planning..Environmental aspects--South Africa